High-dielectric-constant microwave dielectric in the (16–x–y)CaO–xSrO–yBaO–Li2O–Sm2O3–Nd2O3–TiO2 ceramic system - Lin, Ting-Hao; Huang, Ching-Cheng; Hsu, Tsung-Hsien; Huang, Cheng-Liang (Journal of materials science. Materials in electronics, 2024)
This article presents the successful synthesis and characterization of a novel high dielectric constant ceramic system with near-zero temperature coefficient for microwave applications. The system, based on the 5CaO–10SrO–BaO–9Li 2 O–10Sm 2 O 3 –2Nd 2 O 3 –63TiO 2 composition, was developed through a systematic modification of the non-stoichiometric CaO–Li 2 O–Sm 2 O 3 –Nd 2 O 3 –TiO 2 (16:9:10:2:63) ceramic system using the conventional solid-state method. The initial focus of the study was on the effect of Sr substitution for Ca. By varying the Sr content from 1 to 11 mol% and sintering at temperatures ranging from 1120 to 1240 °C, it was observed that increasing Sr substitution led to a higher dielectric constant ( ε r ), while the quality factor multiplied by the resonant frequency ( Q × f ) decreased, and the temperature coefficient of resonant frequency ( τ f ) increased. Notably, at 1180 °C, the optimized composition with 11 mol% Sr substitution (CaO–SrO–Li 2 O–Sm 2 O 3 –Nd 2 O 3 –TiO 2 = 5: 11: 9: 10: 2: 63) achieved a dielectric constant of 140 and an acceptable Q × f value of 1,100 GHz. However, the τ f value was measured as 49.7 ppm/°C, highlighting the need for further optimization for practical applications. To address the issue of the relatively high τ f , 1 mol% of BaO was partially substituted for SrO. This substitution resulted in the formation of a Ba-substituted CSBLSNT phase, which successfully improved the τ f to near-zero while maintaining a moderate ε r . The optimized composition, with a molar ratio of 5: 10: 1: 9: 10:2: 63 for CaO–SrO–BaO–Li 2 O–Sm 2 O 3 –Nd 2 O 3 –TiO 2 , was sintered at 1180 °C for 4 h. The resulting ceramic exhibited excellent dielectric properties: ε r = 132, Q × f = 1,200 GHz, τ f = 5.3 ppm/°C. The combination of a high dielectric constant and near-zero τ f value makes this ceramic system highly promising for the fabrication of smaller, more thermally stable microwave components.